2016
DOI: 10.1177/1090198116677280
|View full text |Cite
|
Sign up to set email alerts
|

Concerns With Entertainment-Education: Zombie Pandemic Preparedness and the Unanticipated Promotion of a Weapons Culture

Abstract: Entertainment-education has proved to be an engaging medium through which to explore health and social issues in populations. Given the popularity of the zombie theme in popular culture it is no surprise therefore that the Centers for Disease Control and Prevention adopted this theme in an effort to engage youth and young adults in emergency preparedness. However, an earlier observational study involving elementary school children based on this premise raised concerns that it may have unexpectedly promoted a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Exploring the latent meaning of the media text, particularly within the context of its production, can reveal ways in which characters or the narrative may affect the convergence of the text encoding and audience decoding, either promoting or hindering effective health communication. Unanticipated consequences of EE approaches to health education due to character portrayals, narratives, and genre have also been reported in other EE studies (Houghton et al, 2017; Tully & Ekdale, 2014). For example, a zombie-based narrative created to promote emergency preparedness unintentionally promoted a focus on firearms (Houghton et al, 2017).…”
Section: Evaluation Of Entertainment Educationsupporting
confidence: 59%
See 2 more Smart Citations
“…Exploring the latent meaning of the media text, particularly within the context of its production, can reveal ways in which characters or the narrative may affect the convergence of the text encoding and audience decoding, either promoting or hindering effective health communication. Unanticipated consequences of EE approaches to health education due to character portrayals, narratives, and genre have also been reported in other EE studies (Houghton et al, 2017; Tully & Ekdale, 2014). For example, a zombie-based narrative created to promote emergency preparedness unintentionally promoted a focus on firearms (Houghton et al, 2017).…”
Section: Evaluation Of Entertainment Educationsupporting
confidence: 59%
“…Unanticipated consequences of EE approaches to health education due to character portrayals, narratives, and genre have also been reported in other EE studies (Houghton et al, 2017; Tully & Ekdale, 2014). For example, a zombie-based narrative created to promote emergency preparedness unintentionally promoted a focus on firearms (Houghton et al, 2017). In this context, textual analysis can identify which images, characters, narratives, or how the zombie genre itself may have implicitly promoted the use of firearms.…”
Section: Evaluation Of Entertainment Educationsupporting
confidence: 59%
See 1 more Smart Citation
“…Emotive storylines can also guide behaviour (Dillard and Meijinders, 2002) through a gateway effect (Borum Chattoo and Feldman, 2017). In this way, entertaining or positive documentary narratives can lead to audiences trusting the media message more (Borum Chattoo and Feldman, 2017; Campolo, 2012), while negative documentary narratives can lead to heightened inclinations to discuss issues (Landreville and LaMarre, 2011) and narratives with fearful messages can lead to increased levels of paranoia (Houghton et al, 2017).…”
Section: Strategic Impact Documentarymentioning
confidence: 99%
“…A previous publication suggested the use of graphic novels could enhance understanding of material ( 5 ). The Centers for Disease Control recently released a zombie graphic novel to raise awareness of disaster preparedness, but at least one study suggested it did not work as hoped ( 6 ) and could even backfire in some aspects ( 7 ). Whether Surgeon X will appeal to the masses is uncertain, but I recommend it as a useful addition to a Biology instructor’s repertoire as a novel way to consider issues regarding the potential post-antibiotic future.…”
mentioning
confidence: 99%